Discovery of the Novel Entecavir‐Resistant Hepatitis B Virus Reverse Transcriptase A181C Substitution From an Integrated Genotypic Analysis. Issue 9 (21st August 2018) - Rose, Ronald E.; Hernandez, Dennis; Falk, Paul J.; Ericson, Karen; Zhou, Nannan; Thiry, Alexandra; McPhee, Fiona
Abstract : Entecavir (ETV) is a first‐line therapy for chronic hepatitis B virus (HBV), demonstrating potent suppression of HBV DNA and a high barrier to viral resistance. Previous studies revealed that ETV‐resistant (ETVr) HBV DNA resulted from substitutions in the HBV reverse transcriptase (RT) at positions rtT184, rtS202, or rtM250 in combination with lamivudine resistance (LVDr) substitutions rtM204I/V±rtL180M. In vitro, viral variants exhibit varying degrees of ETV susceptibility and replication capacity depending on specific resistance substitutions. To explore the potential for additional pathways to ETVr, HBV RT sequences from 982 evaluable patients enrolled in 17 ETV clinical studies were analyzed. Thirty novel emergent substitutions at amino acid positions not previously associated with HBV nucleos(t)ide drug resistance were observed in at least 2 patients and were identified in patient‐derived HBV with a wild‐type, LVDr, or ETVr RT sequence. Phenotypic analysis of these substitutions indicated that they had no effect on ETV susceptibility. Phenotypic analysis was also performed on patient‐derived HBV RT sequences from 10 LVD‐naive and 13 LVD‐experienced patients with virologic breakthrough and emergent novel substitutions while on ETV treatment. One LVD‐experienced patient‐derived HBV RT harboring LVDr substitutions rtL180M+rtM204V with rtA181C displayed reduced ETV susceptibility (122‐fold greater than wild‐type HBV) and remained susceptible to adefovir and tenofovir. HBV harboring the rtA181C substitution without LVDr substitutions rtL180M+rtM204V remained susceptible to inhibition by ETV, adefovir, and tenofovir, although cross‐resistance to LVD and telbivudine was observed. Conclusion: An integrated genotypic analysis of HBV RT sequences from patients with chronic HBV treated with ETV led to the discovery of the novel ETVr substitution rtA181C. This substitution was always detected in combination with LVDr substitutions rtL180M+rtM204V in ETV‐treated patients.